2015
DOI: 10.1515/oere-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Thermograpic study of upper extremities in patients with cerebral palsy

Abstract: Trophic disorders like reduced skin blood circulation are well−known epiphenomenon of cerebral palsy (CP). They can influence quality of life and can lead to skin damages and, as a consequence, to decubitus. Therefore, it is important to analyse temperature regulation in patients with CP. Thermal imaging camera FLIR BCAM SD was used to study the dependency of skin blood circulation in upper extremities of patients with CP on hand dominance, hand force and hand volume. The hand force was evaluated using a conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…In contrast, in order to assess upper limbs temperature regulation on cerebral palsy patients, Lampe et al (2015) performed a thermographic evaluation of the forearm thermal recovery, after cold provocation. It was confirmed that healthy participants had a better forearm thermal recovery than the cerebral palsy patients.…”
Section: Complementary Tool For Pathology Assessmentmentioning
confidence: 99%
“…In contrast, in order to assess upper limbs temperature regulation on cerebral palsy patients, Lampe et al (2015) performed a thermographic evaluation of the forearm thermal recovery, after cold provocation. It was confirmed that healthy participants had a better forearm thermal recovery than the cerebral palsy patients.…”
Section: Complementary Tool For Pathology Assessmentmentioning
confidence: 99%
“…The knowledge on problems with skin blood circulation and increased warm-up times should be noticed by people who take care of persons with disabilities especially patients with lower mobility level. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Cold extremities and poor peripheral BF found in children with CP are relatively associated with the malfunction of ANS. 11 Interferential electrical stimulation that deeply penetrates the body may reinstate BF by sympathetic nervous system adjustment. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Нарастание асимметричности термопаттерна туловища после двигательной нагрузки за счет снижения температуры на стороне патологии зафиксировано у пациента с гемиплегией [30]. О сниженной температуре конечностей, особенно их дистальных отделов, у детей с тяжелыми формами двигательных нарушений сообщают многие исследователи [31][32][33]. Высказано предположение, что периферическая гипотермия у этой категории пациентов является следствием дефицита центрального контроля над балансом между симпатической и парасимпатической активностью, что известно как дисавтономия (dysautonomias) [34].…”
Section: Introductionunclassified